1980
DOI: 10.1002/jmor.1051660304
|View full text |Cite
|
Sign up to set email alerts
|

Cytodiffrentiation in the accessory glands of Tenebrio molitor. VI. A congruent map of cells and their secretions in the layered elastic product of the male bean‐shaped gland

Abstract: The morphology of the bean-shaped accessory glands (BAGs) of males of Tenebrio molitor is described. All cells in the secretory epithelium are long and narrow (300-400 mμ × 5 mμ). The seven types of secretory cells are distinguished from one another by the morphology of their secretory granules. Granule substructure varies from simple spheres with homogeneous electrondense contents to complex forms with thickened exterior walls or with crystalline and membranous contents. Individual cell types were mapped by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 61 publications
1
9
1
Order By: Relevance
“…The secretions produced by the male accessory glands of insects are constituted by heterogeneous substances (Odhiambo 1969, Gerber et al 1971, Dailey et al 1980; this is corroborated by the results obtained in this study that showed granules with positive reactions for carbohydrates and proteins simultaneously.…”
Section: Discussionsupporting
confidence: 93%
“…The secretions produced by the male accessory glands of insects are constituted by heterogeneous substances (Odhiambo 1969, Gerber et al 1971, Dailey et al 1980; this is corroborated by the results obtained in this study that showed granules with positive reactions for carbohydrates and proteins simultaneously.…”
Section: Discussionsupporting
confidence: 93%
“…In Orthoptera, the spermatophore is formed by secretions from different accessory gland tubules (Kaulenas 1992;Marchini et al 2009), each tubule producing different proteins. In T. molitor, the spermatophore is produced by a pair of bean-shaped accessory glands, each gland possessing seven types of epithelial cell organized as homogeneous populations (Dailey et al 1980). Each cell type produces a specific product that contributes to a layered secretory plug which contains spermatophorins used in the construction of the spermatophore (Happ 1992).…”
Section: Invertebrate Reproduction and Development 85mentioning
confidence: 98%
“…Surprisingly, little is known about the secretions and tissue structure of the accessory glands of Coleoptera, especially at a fine structural level. To date, information is available from four species only, Leptinotarsa decemlineata (Chrysomelidae) (De Loof and Lagasse 1972), Tenebrio molitor (Tenebrionidae) (Gadzama et al 1977;Dailey et al 1980;Grimes and Happ 1980;, Acanthoscelides obtectus (Bruchidae) (Huignard 1975;Cassier and Huignard 1979), and Bruchidius atrolineatus (Glitho and Huignard 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The granules of cell type 5 are granular while those of cell type 7 contain membranous whorls (Dailey et al, 1980). With the gentler fixation schedule used for immunocytochemistry, inorphological preservation was not optimal (e.g., Fig.…”
Section: Pl 63 Antigen Identity and Organ Specificitymentioning
confidence: 99%